'Public enemy no. 1': Tobacco industry funding for the AIDS response. Issue 1 (1st January 2016) - Smith, Julia; Thompson, Sheryl; Lee, Kelley
Abstract: This article analyzes the history of tobacco industry funding for the AIDS response – a largely ignored aspect of private donor involvement. Primary documents from the Legacy Tobacco Documents Library and AIDS organizations are analyzed, alongside existing literature on the tobacco control and AIDS responses. Research on the tactics of transnational tobacco companies has documented how they have used various charitable causes to subvert tobacco control efforts and influence public health policy. This raises questions, which this paper seeks to answer, about if donations by tobacco companies to AIDS organizations have been used for similar means, and if so how AIDS organizations have responded to tobacco industry overtures. Two examples illustrate how tobacco companies initially tried to use the AIDS response to counter tobacco control measures: (1) During the 1990s, Philip Morris, one of the largest corporate donors of the AIDS response in the USA, used its connections with AIDS organizations to create competition for health resources, improve its reputation, and market tobacco products to the LGBT community; (2) In both Latin America and sub-Saharan Africa, Philip Morris and British American Tobacco championed the AIDS response in order to delegitimize efforts to develop the World Health Organization's Framework Convention on Tobacco Control. However, from the late 1990s onwards, AIDS organizations began to refuse tobacco funding and partnerships – though these policies have been not comprehensive, as many tobacco companies still fund programs in sub-Saharan Africa. The article concludes that tobacco companies aimed to exploit competition between health issues, and use the high-profile AIDS response to improve their reputation and market access. However, AIDS organizations, adhering to broader health goals and drawing on extensive resources and networks, were able to shut the tobacco industry out of much of the response, though pockets of influence still exist. This demonstrates the importance of co-operation and policy convergence across health sectors and suggests that tobacco control advocates, and other charitable sectors that receive funding from the tobacco industry, may be able to draw lessons from the experiences of AIDS organizations.